Analisis Hidrologi untuk Mendapatkan Debit Banjir Rencana Sungai Rua Kota Ternate dalam Perencanaan Sabo DAM Menggunakan HSS Nakayasu - Setyono, Ernawan; Darmawan, Azhar Adi; Islana, Maulana Jibril; Somadayo, M. Muchdi M.; Lisan, Nur Fasichul (Universitas Batanghari Jambi, 2025)
Flash floods are usually caused by heavy rainfall and are extremely destructive. They are rapid and carry dangerous materials such as mud, rocks and wood that can cause casualties in the areas they pass through. The Sabo Dam project in the Rua sub-district was planned to withstand the onslaught of material swept away by flash floods. It has a watershed area of 1.8 km² and a river length of 3.63 km. A hydrological analysis was conducted to provide an overview of the potential for flash flooding in the Rua River. This analysis describes hydrological phenomena such as maximum runoff discharge in order to predict the Sabo Dam's design strength. Maximum runoff discharge was calculated using the Nakayasu HSS method. The results of the data analysis showed that the maximum runoff discharge in the Rua watershed for a 50-year return period was 32.51 m³/second.